2013
DOI: 10.1371/journal.pone.0071002
|View full text |Cite
|
Sign up to set email alerts
|

Fusion of Mature HIV-1 Particles Leads to Complete Release of a Gag-GFP-Based Content Marker and Raises the Intraviral pH

Abstract: By imaging the release of a GFP-based viral content marker produced upon virus maturation, we have previously found that HIV-1 fuses with endosomes. In contrast, fusion at the cell surface did not progress beyond a lipid mixing stage (hemifusion). However, recent evidence suggesting that free GFP can be trapped within the mature HIV-1 capsid raises concerns that this content marker may not be released immediately after the formation of a fusion pore. To determine whether a significant portion of GFP is trapped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
98
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(110 citation statements)
references
References 63 publications
12
98
0
Order By: Relevance
“…Fusion of HXB2pp containing or lacking SER5-HA or SER2-HA culminates in the release of mCherry through fusion pores larger than 4 nm in diameter (Fig. 3, A and B) (28). As expected, SER2-HA-containing particles and control virions fused equally well, whereas fusion of SER5-HA particles was markedly inhibited (Fig.…”
Section: Ser5 But Not Ser2 Inhibits the Formation Of Small Fusion Poressupporting
confidence: 65%
See 2 more Smart Citations
“…Fusion of HXB2pp containing or lacking SER5-HA or SER2-HA culminates in the release of mCherry through fusion pores larger than 4 nm in diameter (Fig. 3, A and B) (28). As expected, SER2-HA-containing particles and control virions fused equally well, whereas fusion of SER5-HA particles was markedly inhibited (Fig.…”
Section: Ser5 But Not Ser2 Inhibits the Formation Of Small Fusion Poressupporting
confidence: 65%
“…HXB2pp were co-labeled with YFP-Vpr and the viral content marker Gag-iCherry containing an "internal" mCherry tag (28). Fusion of HXB2pp containing or lacking SER5-HA or SER2-HA culminates in the release of mCherry through fusion pores larger than 4 nm in diameter (Fig.…”
Section: Ser5 But Not Ser2 Inhibits the Formation Of Small Fusion Poresmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple groups have shown that the generation of HIV-1 particles with a Gag-GFP polyprotein (HIV-iGFP) releases free GFP after proteolytic viral maturation. The liberated GFP then becomes an intravirion fluid phase marker (41)(42)(43). We previously demonstrated that a minority subset of the fluid phase GFP is trapped within the capsid structure (42,44).…”
Section: Development Of a Live-cell Imaging Fluorescent Microscopy Asmentioning
confidence: 99%
“…Single-virus fusion assays were performed by imaging fluorescently labeled ASLVpp entry in CV-1 and A549 cells expressing the TVA950 or TVA800 receptor isoform, based on previous protocols (59,65). Briefly, cells were grown on collagen-coated number 1.5 glass-bottomed Petri dishes (MatTek, MA) up to 90% confluent in FluoroBrite DMEM with 10% FBS.…”
Section: Single-virus Imagingmentioning
confidence: 99%